053 Intracranial pressure determines headache morbidity in idiopathic intracranial hypertension. Issue 6 (27th May 2022) - Mollan, Susan; Wakerley, Ben; Alimajstorovic, Zerin; Mitchell, James; Ottridge, Ryan; Yiangou, Andreas; Thaller, Mark; Grech, Olivia; Brock, Kristian; Sinclair, Alex
Abstract : Objective: Headache is the predominant disabler in idiopathic intracranial hypertension (IIH). The aim was to characterise headache and investigate the association with intracranial pressure (ICP). Methods: IIH:WT was a randomised controlled parallel group multicentre trial investigating weight manage- ment methods in IIH. Participants with active IIH (evidenced by papilloedema) and a body mass index (BMI) ≥35kg/m2 were recruited. At baseline, 12 months and 24 months headache characteristics and quality of life outcome measures were collected and lumbar puncture measurements were performed. Results: Sixty-six women were included (mean age 32.0 years (SD ± 7.8)), and mean body mass index of 43.9 ± 7.0 kg/m2. The headache phenotype was migraine-like in 86%. Headache severity correlated with ICP) at baseline (r=0.285; p=0.024); change in headache severity and monthly headache days correlated with change in ICP at 12 months (r=0.454, p=0.001 and r=0.419, p=0.002 respectively). Cutaneous allodynia was significantly correlated with ICP at 12 months. (r=0.479, p<0.001). Boot strap analysis noted a positive association between ICP at 12 and 24 months and enabled prediction of change in headache severity and monthly headache days. ICP was associated with significant improvements in quality of life (SF-36). Conclusions: We demonstrate a positive relationship between ICP and headache and cutaneous allodynia, which has not been previously reported in IIH. Those with the greatest reduction in ICP had the greatest reduction in headache frequency and severity. soozmollan@doctors.org.uk